2014
DOI: 10.1371/journal.pone.0086881
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Inhibition Blocks ROS-NFκB Signaling and Attenuates Endotoxemia-Induced Liver Injury

Abstract: BackgroundAMP-activated protein kinase (AMPK) is an important enzyme in regulation of cellular energy homeostasis. We have previously shown that AMPK activation by 5-aminoimidazole-4-carboxamide (AICAR) results in suppression of immune responses, indicating the pivotal role of AMPK in immune regulation. However, the cellular mechanism underpinning AMPK inhibition on immune response remains largely to be elucidated. The study aimed to investigate the effects of AMPK inhibition on reactive oxygen species (ROS)-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…However, the relationship between the AMPK pathway and CD68 expression in the phenotype differentiation of monocytes/macrophages is rarely understood. A recent study of animal models of endotoxemia-induced liver injury demonstrated that AICAR, an AMPK activator, or Compound C, an AMPK inhibitor, could attenuate LPS-induced CD68 expression [42]. Our results suggested that HUA exposure can also activate the AMPK pathway and attenuate CD68 expression in cell differentiation, but Compound C can reverse this effect.…”
Section: Discussionsupporting
confidence: 47%
“…However, the relationship between the AMPK pathway and CD68 expression in the phenotype differentiation of monocytes/macrophages is rarely understood. A recent study of animal models of endotoxemia-induced liver injury demonstrated that AICAR, an AMPK activator, or Compound C, an AMPK inhibitor, could attenuate LPS-induced CD68 expression [42]. Our results suggested that HUA exposure can also activate the AMPK pathway and attenuate CD68 expression in cell differentiation, but Compound C can reverse this effect.…”
Section: Discussionsupporting
confidence: 47%
“…Confusingly, both AMPK activation and inhibition using synthetic agents have been shown to decrease LPS-induced liver injury (33). To clarify the results obtained by pharmacologically manipulating AMPK, genetic AMPK mutants were employed (34).…”
Section: Discussionmentioning
confidence: 99%
“…A potential limitation of the present study is the heavy reliance on pharmacological agents to dissect signaling pathways [e.g., compound C, STO-609, and Zn(II)PPIX], leaving open the possibility for off-target effects. However, at the concentrations used, the compounds [STO-609 (5 mM), compound C (10 mM), and Zn(II)PPIX (5 mM)] are likely to have acted relatively specifically (Zhou et al, 2007;Nowis et al, 2008;Reihill et al, 2011;Guo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%